Media Sosial dan Wacana penundaan Pemilu 2024 Dalam Perspektif Norman Fairclough - Aminudin, Amin (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
The discourse on postponing the elections in 2024 is considered a strategy to vent the political appetites of today's rulers who enjoy the opium of power, social media as a space for expression has become a hotly discussed discourse battle, including discussions about postponing the 2024 elections. The formulation of theproblem in this research is the purpose of this study is to find out how social media power relations have become a space to fight for discourse on postponing the 2024 general election?. The method used in this study is a qualitative method with a critical discourse analysis theory approach from Norman Fairclough. The paradigm used in this study is the critical paradigm. The data collection technique uses the content analysis method, this method is carried out by analyzing uploads on social media related to the postponement of the 2024 election. The results show that the discourse on postponing the election can be seen in 3 things: First, the narrative/news text used by Twitter social media users not just news texts, but nuanced arguments and descriptions, as was conveyed by Denny Indrayana who is more argumentative than his concern about the alleged postponement of elections and extending the term of office of the rulers. Second, discourse on social media, especially Twitter, tends to raise controversial issues in Indonesia, the issue of controversy in question is that there is an alleged effort against the law and tends to be political, meaning that the interests of the content creator are more dominant than balanced reporting. The last one is that when viewed from an ideological aspect, social media Twitter provides a negative image by cornering the country's rulers, in this case the government leader during President Jokowi's era, so that the public evaluates negatively the actionstaken by a group of people from the palace.